1983
DOI: 10.1136/thx.38.10.771
|View full text |Cite
|
Sign up to set email alerts
|

Plasma histamine in asthmatic and control subjects following exercise: influence of circulating basophils and different assay techniques.

Abstract: Arterial plasma histamine concentrations were measured after exercise in 10 subjects with extrinsic atopic asthma, 10 who were non-atopic and non-asthmatic and seven who were atopic but non-asthmatic, by a single isotope radioenzymatic assay. Significantly higher plasma histamine concentrations were found in the asthmatic subjects before exercise than in the nonatopic controls (p < 0-05). The mean histamine concentration rose after exercise in all groups but the increased levels were not significantly differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…This confusion is probably due to the technical difficulties with measuring small changes in circulating concentrations of histamine following exercise. Since the basophil is another potential source of histamine, it has been suggested that the increases in plasma or whole-blood histamine can be attributed to the basophilia which ensues exercise [20,39]. However, NAGAKURA et al [40] demonstrated a rise in histamine that was restricted to those who had experienced EIB, despite the fact that both EIB-positive and EIB-negative asthmatics had similar postexercise basophilia.…”
Section: Discussionmentioning
confidence: 98%
“…This confusion is probably due to the technical difficulties with measuring small changes in circulating concentrations of histamine following exercise. Since the basophil is another potential source of histamine, it has been suggested that the increases in plasma or whole-blood histamine can be attributed to the basophilia which ensues exercise [20,39]. However, NAGAKURA et al [40] demonstrated a rise in histamine that was restricted to those who had experienced EIB, despite the fact that both EIB-positive and EIB-negative asthmatics had similar postexercise basophilia.…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that exercise causes histamine release; however, this is difficult to assess in humans as red blood cells actively take up histamine (Campos et al 1999). Histamine levels have been measured in arterial and venous whole blood as well as venous plasma during and after high‐intensity exercise (Duner & Pernow, 1958; Harries et al 1979; Hartley et al 1981; Morgan et al 1983; Campos et al 1999). However, these studies do not agree on an adequate method for collecting and analysing the concentration of histamine.…”
Section: Discussionmentioning
confidence: 99%
“…The potential involvement of histamine is evidenced from two sets of data. First is the observation of elevated plasma histamine levels in stable asthma (37)(38)(39); consistent with this is the long recognized weak bronchodilator actions of both the older and newer antihistamines (40)(41)(42)(43)(44)(45). Second are the observations under experimental conditions that elevated plasma histamine levels accompany bronchoconstriction following provocation with allergen (46,47), exercise (48)(49) and adenosine (50) but not isocapnic hyperventilation (51).…”
Section: Antihistamines As Inhibitors Of Early-phase Allergic Responsesmentioning
confidence: 66%